2015
DOI: 10.1111/pcn.12272
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among medication adherence, insight, and neurocognition in chronic schizophrenia

Abstract: Aims:In order to improve long-term prognosis in schizophrenia, enhancing medication adherence is essential. The aim of this study was thus to identify the association between medication non-adherence and possible risk factors in a large sample of patients with chronic schizophrenia. Methods:One hundred and four patients with schizophrenia with a disease duration of over 10 years were enrolled in this cross-sectional study. The subjects were assessed with the Scale to Assess Unawareness of Mental Disease-Korean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
(50 reference statements)
5
15
0
3
Order By: Relevance
“…Consistent with this, Misdrahi et al 18 and Lincoln et al 19 found that persons with poor insight were more likely to refuse to take antipsychotic medication, while others have found that groups with lower levels of adherence across cultures have consistently tended to have poorer clinical insight [20][21][22][23] .…”
Section: Insight and Treatment Engagementsupporting
confidence: 59%
“…Consistent with this, Misdrahi et al 18 and Lincoln et al 19 found that persons with poor insight were more likely to refuse to take antipsychotic medication, while others have found that groups with lower levels of adherence across cultures have consistently tended to have poorer clinical insight [20][21][22][23] .…”
Section: Insight and Treatment Engagementsupporting
confidence: 59%
“…Results from a cross-sectional study of Korean patients with chronic schizophrenia reported that poor executive function was a significant predictor of nonadherence; however, other cognitive functions, such as long-term memory, perception, and attention with working memory, were not significant 36. Forgetfulness was the most common reason for nonadherence self-reported by poorly adherent patients with schizophrenia and related disorders in Ethiopia39 and by patients with bipolar disorder 43.…”
Section: Resultsmentioning
confidence: 94%
“…When a specific domain of insight was assessed, awareness of need for treatment but not awareness of illness was significantly associated with adherence in patients with schizophrenia and schizoaffective disorder 47. Similarly, poor awareness of need for treatment was associated with poor adherence in Korean patients with chronic schizophrenia 36. In contrast, a study from Ethiopia found that awareness of illness and ability to positively reassess experiences/symptoms, but not awareness of need for treatment, were associated with better adherence in patients with schizophrenia 35.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As in the case of symptoms, a complicating factor is that poor neurocognition could also contribute to treatment non-adherence, creating another feedback loop through which symptoms and insight could be related. Indeed, a recent study found that better executive functioning and better insight were associated with increased medication adherence [64].…”
Section: Neurocognition and Anomalous Brain Structure And Functionmentioning
confidence: 99%